Transformasi Arsitektur Fasilitas Pengolahan Sampah sebagai Infrastruktur Perkotaan Berkelanjutan - Aris Budhiyanto; Oswynn Susanto (Jurnal Teknologi dan Desain, 2026)
Waste treatment facilities are traditionally perceived as closed and polluting industrial buildings, detached from urban life. However, within sustainable city frameworks, such facilities play a crucial role in environmental health and urban systems. This study employs a qualitative method with a comparative case study approach, examining three projects: CopenHill, Shenzhen Energy Ring, and Kamikatsu Zero Waste Center. These cases were selected based on differences in context and waste-processing typology. The analysis is conducted using variables including architectural aspects, environmental strategies, contextual integration, functional zoning, and spatial circulation. Data were collected through literature review and design documentation, and analyzed using a descriptive-comparative method to produce a synthesis of findings. The results indicate that architectural strategies in waste management facilities are strongly influenced by context and scale, yet share common principles. First, the integration of industrial and public functions can be achieved through clear zoning and circulation without compromising technical performance. Second, environmental strategies are implemented through a combination of passive and active systems to minimize ecological impact. Third, building form and configuration are shaped by contextual responses rather than purely visual expression. Fourth, architecture serves as an educational medium through spatial openness and user engagement. This study formulates design principles that can serve as a reference for developing waste management facilities that are not only technically efficient but also environmentally integrated and sustainable within the urban system.